Exploring the contribution of business and technology incubators to women entrepreneurs' business development in Dar es Salaam, Tanzania - Alsen Florian Kapinga; Calkin Suero Montero; Godfrey Issac Mwandosya; Esther Rosinner Mbise (Journal of Global Entrepreneurship Research, 2018)
Women entrepreneurs are key players in the economic development of societies in Sub-Saharan Africa. However, research has reported that business and technology incubators offer insufficient support to their enterprises. Consequently, this paper sets out to explore and highlight the present status of the contribution of business and technology incubators to women entrepreneurs' businesses. The study collected data through exploratory focus group discussions, in-depth interviews, and structured questionnaires. The data were analysed and interpreted using the convergent parallel method. The findings indicate that business incubators provide women's business with training and to some extend enhance their access to market information and business networks. However, the study also finds a lack of contextualisation in the business and technology incubators' services to the real needs of the incubatees, which eventually makes their support less impactful. In this light, the study recommends the provision of incubators' services tailored to the real needs of women businesses. Our work puts forward recommendations to support women entrepreneurs' business development through the contextualisation of the incubators' services tailored to the incubatees' real needs including appropriate training beyond business management. Further investments for establishing new incubation centres are also recommended.
Keywords: 650; Women entrepreneurs; Development; Business incubator; Tanzania